ANALISIS EFISIENSI PRODUKSI DAN KEUNTUNGAN USAHATANI JAGUNG DI KABUPATEN OGAN KOMERING ULU TIMUR SUMATERA SELATAN - Ongki Fermadi; Fembriarti Erry Prasmatiwi; Eka Kasymir (Lampung University, 2015)
This research aims to: identify the factors that affect corn’s farming, analyze the efficiency of corn production and know the advantages of corn’s farming in East Ogan Komering Ulu Regency of South Sumatera. This research was located in Bunga Mayang and Jayapura Subdistrict of East Ogan Komering Ulu Regency. The Farmer respondets were drawn by simple random sampling. The data was analyzed by Cobb-Douglas production function, production analysis by using value of NPMxi/Pxi and farmer profit analysis. The results showed that production of maize farming in the District of East OKU in the year of 2012-2013 were affected by land area (X1), seeds(X2) and labor(X5). Technically, the use of inputs in corn farming in the study site was in the region I (increasing returns to scale); thus, it was considered as inefficient use of inputs. Corn farming in the District of East OKU was profitable in which R/C >1 and the revenue generated was Rp17,014,306.00/hectare. Key words :corn, efficiency, production, production efficiency